2013
DOI: 10.1186/1476-9255-10-14
|View full text |Cite
|
Sign up to set email alerts
|

The anti-idiotypic antibody 1F7 stimulates monocyte interleukin-10 production and induces endotoxin tolerance

Abstract: BackgroundPathogens that establish chronic infection elicit immune responses with suppressive cytokines dominating over pro-inflammatory cytokines. Chronic hepatitis C virus (HCV) infection, human immunodeficiency virus (HIV) infection and simian immunodeficiency virus (SIV) infection are associated with high levels of antiviral antibodies expressing a common idiotype specifically recognized by the 1F7 monoclonal antibody (mAb). The 1F7 mAb is a murine IgMκ antibody raised against immunoglobulin pooled from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…AId is employed as a vaccine, as potential serodiagnosis reagents in immunoassays and substations of highly toxic substances (Deyev & Lebedenko, 2009;Hu et al, 2017;Koprowski, Herlyn, Lubeck, DeFreitas, & Sears, 1984;Ruffini et al, 2014). In recent years, anti-idiotypic antibody technology has been used to prepare vaccines for hepatitis A, B, C and various diseases (Davtyan, Poghosyan, Sukiasyan, & Grant, 2013;Grant, 2002;Kiyohara et al, 2009;Yildirim, Başalp, Yücel, Manav, & Sezen, 2004). Eger et al (2016) also reported that a new human/mouse chimeric anti-idiotype Ab ganglidiximab may have the potential to tailor immune responses to the paratope regions mimicking GD2 overexpressed in neuroblastoma (NB) as well.…”
Section: Introductionmentioning
confidence: 99%
“…AId is employed as a vaccine, as potential serodiagnosis reagents in immunoassays and substations of highly toxic substances (Deyev & Lebedenko, 2009;Hu et al, 2017;Koprowski, Herlyn, Lubeck, DeFreitas, & Sears, 1984;Ruffini et al, 2014). In recent years, anti-idiotypic antibody technology has been used to prepare vaccines for hepatitis A, B, C and various diseases (Davtyan, Poghosyan, Sukiasyan, & Grant, 2013;Grant, 2002;Kiyohara et al, 2009;Yildirim, Başalp, Yücel, Manav, & Sezen, 2004). Eger et al (2016) also reported that a new human/mouse chimeric anti-idiotype Ab ganglidiximab may have the potential to tailor immune responses to the paratope regions mimicking GD2 overexpressed in neuroblastoma (NB) as well.…”
Section: Introductionmentioning
confidence: 99%